The plurality of blocks in a condominium and the condominium owners’ diligence towards the builder - Gil MOREIRA DOS SANTOS (Revista Jurídica Portucalense, 2025)
On the subject of a judgment - Pº 24620/15.1T9PRT- P1 of the 5th Chamber of the Court of Appeal of Porto, dated 08.04.2024 - in which the institutions of the forfeiture of the notice of defects in a construction contract relating to a condominium of four blocks, to be built in several phases, were discussed.